2006
DOI: 10.1007/s10488-006-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Incentives to Improve Client Retention in an Outpatient Substance Abuse Aftercare Program

Abstract: Pay for performance, the provision of financial incentives for favorable performance, is increasingly under study as an evidence-based practice. This study estimated the improvement in client retention from offering incentives to 11 substance abuse counselors providing outpatient aftercare treatment. During the incentive period, a counselor could earn a bonus of $100, in addition to his regular compensation, for each client who completed at least five aftercare sessions (the "milestone" which we considered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…The work of Lash et al (2007), Chutuape et al (2001), and Shepard et al (2006) suggests that engagement and retention in continuing care can be increased with relatively low cost, low effort approaches, which can be applied to virtually any continuing care protocol. This points to the potential benefit of conducting research to identify evidence based practices that are easily exported, in addition to the continued search for evidence based continuing care treatments.…”
Section: 0 What Can We Conclude From These Results?mentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Lash et al (2007), Chutuape et al (2001), and Shepard et al (2006) suggests that engagement and retention in continuing care can be increased with relatively low cost, low effort approaches, which can be applied to virtually any continuing care protocol. This points to the potential benefit of conducting research to identify evidence based practices that are easily exported, in addition to the continued search for evidence based continuing care treatments.…”
Section: 0 What Can We Conclude From These Results?mentioning
confidence: 99%
“…Schmitt, Phibbs, and Piette (2003) found that patients who lived within 10 miles of a continuing care facility were 2.6 times more likely to seek treatment there following discharge from residential treatment than those who lived at least 50 miles from the facility. Finally, Shepard and colleagues found that providing continuing care counselors with a $100 bonus for each of their patients who attended at least 5 sessions of continuing care raised the percentage of patients who achieved that milestone from 33% to 59% (Shepard et al, 2006). …”
Section: 0 Findings From Studies Of Continuing Carementioning
confidence: 99%
“…One method recommended by the Institute of Medicine (IOM; Institute of Medicine, 2007) to improve the quality of healthcare is pay-for-performance (P4P). Shepard and colleagues (2006) showed that providing financial incentives to therapists could be an effective and cost-effective approach to improve client retention. Although these practices have become increasingly common in healthcare, few studies have examined the impact of P4P methods experimentally (Dudley, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Contingent upon further predictive validation of its relationship to important client treatment outcomes (e.g., reduced substance use and criminal activity), achievement of continuity of care could potentially serve as an important target criterion upon which providers are not only held accountable for, but also rewarded for achieving (i.e., pay-for-performance [P4P]). Indeed, P4P is one approach that has been recommended by the Institute of Medicine (2007) and is has been applied in both general medicine (Rosenthal & Dudley, 2007; Rosenthal, Landon, Normand, Frank, & Epstein, 2006) and the substance abuse treatment field (Garner et al, 2009; McLellan, Kemp, Brooks, & Carise, 2008; Shepard et al, 2006). Second, as approximately 8 out of 10 AC participants met the WC criterion for continuing care initiation it suggests continuity of care can be achieved with significantly more adolescents than only those who are sufficiently motivated, organized, and resourced to attend clinic appointments.…”
Section: Discussionmentioning
confidence: 99%